Analisis Vegetasi Gulma pada Perkebunan Kelapa Sawit (Elais quineensis jacq.) di Kilangan, Muaro Bulian, Batang Hari - Ade Adriadi; - Chairul; - Solfiyeni (Jurnal Biologi Universitas Andalas, 2012)
A vegetation analysis of weed in palm oil plantation (Elaeis quineensis Jacq.) in Kilangan Muaro Bulian, Batang Hari has been conducted from February to May 2012 by using quadrate method. Twenty four – 1 m2 plots were placed using purposive sampling method. The result showed that weed composition in palm oil plantation composed by 20 families, 47 genera, 56 spesies and 3934 individuals. Paspalum conjugatum was highest SDR 19.48% (1029 individuals), and the lowest was Cuphea platycentra SDR 0,19% (2 individuals) in palm oil plantation. Index diversity of weed was H’ = 3.14.Keywords : Elaeis quineensis Jacq, composition, structure